2016
DOI: 10.15252/embr.201643453
|View full text |Cite
|
Sign up to set email alerts
|

Plants get on PAR with poly( ADP ‐ribosyl)ation

Abstract: PARylation, was first described over 50 years ago. Since then, our understanding of the biochemistry and enzymology of this protein modification has significantly progressed. PARylation has long been associated with DNA damage and DNA repair as well as genotoxic stress [1,2]. However, over the last two decades this has expanded to chromatin remodelling, DNA replication, transcriptional regulation, telomere cohesion and mitotic spindle formation during cell division, intracellular trafficking and energy metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…In plants, a mechanistic understanding of the role of ADP-ribosylation in stress response is still lacking, as well as in plant interaction with bacteria [74]. In 2016, Feng et al identified the first set of non-histone plant PARylated proteins, showing that in vivo PARylation of DAWDLE (DDL) is important in plant immunity [75,76]. DDL, a Forkhead associated (FHA) domain protein, domain that may bind to PAR polymer and to phosphothreonine, is involved in plant immunity, in a pathway downstream to PARP-domain activity and upstream to activation of gene expression of defense-related proteins [76].…”
Section: Plants: Role Of Nad + and Parp Domain Enzymes In Immune Respmentioning
confidence: 99%
“…In plants, a mechanistic understanding of the role of ADP-ribosylation in stress response is still lacking, as well as in plant interaction with bacteria [74]. In 2016, Feng et al identified the first set of non-histone plant PARylated proteins, showing that in vivo PARylation of DAWDLE (DDL) is important in plant immunity [75,76]. DDL, a Forkhead associated (FHA) domain protein, domain that may bind to PAR polymer and to phosphothreonine, is involved in plant immunity, in a pathway downstream to PARP-domain activity and upstream to activation of gene expression of defense-related proteins [76].…”
Section: Plants: Role Of Nad + and Parp Domain Enzymes In Immune Respmentioning
confidence: 99%